SAT0493 Farber Disease: First Natural History Cohort Demonstrates a Broad Clinical Spectrum with Implications for Juvenile Idiopathic Arthritis Patients. (9th June 2015) - Solyom, A.; Ehlert, K.; Hügle, B.; Magnusson, B.; Grigelioniene, G.; Guelbert, N.; Gardner-Medwin, J.; Tanpaiboon, P.; Jung, L.; Puri, R.; DiRocco, M.; Mitchell, J.; et al.
Abstract : Background: Farber disease (Farber lipogranulomatosis; acid ceramidase deficiency) is a rare lysosomal storage disorder resulting from the inherited deficiency of the enzyme acid ceramidase, and the accumulation of the lipid substrate, ceramide. Ceramide is a potent pro-inflammatory and pro-apoptotic lipid. The moderate phenotype generally includes joint swelling, contractures and pain. The clinical similarity of the moderate Farber phenotype to polyarticular juvenile idiopathic arthritis (JIA) can lead to misdiagnosis. Differential diagnosis can be made by accounting for the comparatively early onset, progressive symmetric arthritis, presence of subcutaneous nodules, and an unusual, hoarse voice (due to nodule formation on the larynx) in Farber disease patients. Objectives: The analysis of clinical information from a cohort of Farber disease patients to better define the overlap with juvenile idiopathic arthritis. Methods: A cohort of 25 living Farber disease patients has been established to provide insight into the phenotypic spectrum of the disease, as well as the clinical history, diagnostic evaluations, and treatments the patients have undergone. Retrospectively, whenever possible, the presenting symptoms, clinical history, biochemical, and genetic diagnostic evaluations were recorded. Treatment modalities and response to treatment were registered. Results: Patients in the cohort vary in age from 5 months to 33 years of age. Phenotypes range from infantile onset with systemic inflammation, to late childhood onset and very mild disease. Most patients demonstrated the three typical symptoms of Farber disease (arthritis, subcutaneous nodules, dysphonia). However, in several cases years passed between appearance of the individual symptoms. Treatment varied from haematopoietic stem cell transplantation, to biologics (incl. anti-TNFa and anti-IL-6) and intensive pain relief, to no treatment at all. Conclusions: This study represents the largest collection of clinical data on Farber disease to date. It is clear that the spectrum of phenotypes includes mild presentations not previously associated with Farber, and that in most cases a pediatric rheumatologist is involved in patient care. The fact that 25 patients could be collected over 6 months implies that the disease is not as rare as earlier supposed. These results also suggest that acid ceramidase deficiency may likely account for a larger number of polyarticular JIA patients than previously thought. It is therefore important to increase awareness of Farber disease among rheumatologists. The screening process will be greatly simplified with the use of dried blood spot assays. Enzyme replacement therapy for Farber is currently under development. Disclosure of Interest: A. Solyom Grant/research support from: Plexcera Therapeutics LLC, Consultant for: Plexcera Therapeutics LLC, K. Ehlert: None declared, B. Hügle: None declared, B. Magnusson: None declared, G. Grigelioniene: None declared, N. Guelbert: None declared, J. Gardner-Medwin: None declared, P. Tanpaiboon: None declared, L. Jung: None declared, R. Puri: None declared, M. DiRocco: None declared, J. Mitchell: None declared, M. Beck: None declared, C. Simonaro: None declared, E. Schuchman Shareholder of: Plexcera Therapeutics LLC